ANALISIS PELAKSANAAN 10 PROGRAM POKOK PEMBERDAYAAN KESEJAHTERAAN KELUARGA (PKK) DI DESA SUKADAMAI KECAMATAN UJUNGBATU KABUPATEN ROKAN HULU - Hayati, Fuji Khusnul; Irja, Desti; Natuna, Daeng Ayub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Based on the observations done by researcher in the field then researcher get the phenomena faced by activator team of family welfare empowerment (PKK) sukadamai village at the time of implementation that is: there is still any some PKK members who don't understand and don't even know about 10 main program of PKK which must be done by PKK. The implementation of other community activities and maternal & child health centre (Posyandu) is still lack of support from the RT and RW, the lack of public participation on community activities. The purpose of this research is to know the execution of 10 main program of PKK in sukadamai village ujungbatu subdistrict of Rokan Hulu regency. This research used qualitative methods by using a descriptive approach. The results of this research showed that 1. Comprehension and implementing pancasila in practice is very good, 2. Implementation of mutual aid (gotong royong) is very good, 3. Food was implemented well enough, 4. Clothing has done very good 5. Housing and the implementation of households, have been implemented with good, 6. Education and skills is already done good, 7. Health is already done good, 8. development of cooperative life have been implemented with good 9. Environmental Sustainability was done good, 10. healthy Planning has been implemented with good.Key words: Analysis, 10 Programs PKK, PKK